Aniołowie w pierwszym łacińskim komentarzu do Apokalipsy Wiktoryna z Petowium - Budzanowska-Weglenda, Dominika Łucja (Vox Patrum, 2023)
The purpose of this article is to examine how Victorinus of Poetovium (Poetavium), in his Commentarius in Apocalypsim, comments on the passages in the Apocalypse of St John in which the term ‘angel’ – angelus – occurs, and how he interprets the term. First, the frequent occurrence of angels in Scripture, especially in the last book of the Bible, is mentioned. It was recalled, following Augustine of Hippo, that the term angelus denotes a mission and not the nature of the beings so termed. It was also stressed that, for the Church Fathers, angelology was not the most important issue addressed in their writings, and similarly, it is quite rare for scholars to deal with the patristic teaching on angels. A brief introduction is given to Bishop Victorinus as the first Latin exegete and his style of interpretation, especially the importance of alegoresis and typology. All explanations of the term angelus in the extant fragments of Victorinus’ commentary on the Apocalypse are discussed: first those in which angel is taken to mean Elijah or Christ himself, then the good heavenly angels, and finally the evil angels – the devil, the Antichrist – are analysed. The results of a study of another text by the Bishop of Poetovium, De fabrica mundi, are also briefly quoted, in which this treatise on the creation of the world contains interesting concepts by the author about angels, concerning, for example, the twenty-four original angels created on the first day.